Impact of visit-to-visit glycemic variability on the risks of macrovascular and microvascular events and all-cause mortality in type 2 diabetes: the ADVANCE trial - Hirakawa, Yoichiro; Arima, Hisatomi; Zoungas, Sophia; Ninomiya, Toshiharu; Cooper, Mark; Hamet, Pavel; Mancia, Giuseppe; Poulter, Neil; Harrap, Stephen; Woodward, Mark; Chalmers, John (Diabetes care, 2014)
There is no consensus on the importance of visit-to-visit glycemic variability in diabetes. Therefore, we assessed the effects of visit-to-visit variability (VVV) in HbA1c and fasting glucose on major outcomes in the ADVANCE (Action in Diabetes and Vascular Disease: Preterax and Diamicron MR Controlled Evaluation) trial. ADVANCE was a factorial randomized controlled trial of intensive glucose control and blood pressure lowering in patients with type 2 diabetes. VVV in the intensive glucose treatment group was defined using the SD of five measurements of HbA1c and glucose taken 3-24 months after randomization. Outcomes were combined macro- and microvascular events and all-cause mortality occurring post 24 months. Sensitivity analyses were performed using other indices of variability and in the standard glucose treatment group. Among 4,399 patients in the intensive group, an increase in VVV of HbA1c was associated with an increased risk of vascular events (P = 0.01) and with mortality (P < 0.001): highest versus lowest tenth hazard ratio (95% CI) 1.64 (1.05-2.55) and 3.31 (1.57-6.98), respectively, after multivariable adjustment. A clear association was also observed between VVV of fasting glucose and increased risk of vascular events (P < 0.001; 2.70 [1.65-4.42]). HbA1c variability was positively associated with the risk of macrovascular events (P = 0.02 for trend), whereas glucose variability was associated with both macro- and microvascular events (P = 0.005 and P < 0.001 for trend, respectively). Sensitivity analyses using other indices, and patients in the standard glucose treatment group, were broadly consistent with these results. Consistency of glycemic control is important to reduce the risks of vascular events and death in type 2 diabetes.